THE IDEOLOGICAL AND ARTISTIC ORIGINALITY OF THE STORIES OF ALIM TEPPEYEV - SARBASHEVA, A.M. (Kavkazologiya, 2021)
The article is devoted to the study of the ideological and artistic features of A. Teppeev's short prose in the aspect of identifying the main problem-thematic trends in its development. The paper notes the influence of the aesthetic experience of the classics of Russian literature on the formation of the creative worldview of national writers of the second half of the twentieth century. The main objects of artistic and philosophical understanding (the spiritual world and the search for heroes, moral values) in the stories of A. Teppeev of the period of the 1960s-1980s are determined. The role of the artistic symbol in the structure of the narrative is considered, the content-aesthetic dominants, the ethno-cultural specificity of the works are revealed. Against the background of the motivational and thematic diversity (the motives of doom – "The Bridge of the Humpback Geuz", "Kara", the inevitability of fate – "Bitter Earth drink", "Target", the collisions of love – "Unconquered Peaks", "Whitefly"), the key task of the writer is determined-the artistic understanding of the spiritual and moral potential of a person in the context of historical time (Civil War, Great Patriotic War, modernity). As a result of the work carried out, a conclusion is made about the ideological and artistic originality of the stories of A. Teppeev, expressed in deep psychologism, in the actualization of the spiritual and moral principle (the image of the evolution/degradation of the characters who find themselves in dramatic circumstances, in situations of moral choice between good and evil, honor and dishonor, loyalty and betrayal), in the creative originality of the solution of moral and ethical, philosophical problems of human existence.